The Wiley Handbook on the Theories, Assessment and Treatment of Sexual Offending 2016
DOI: 10.1002/9781118574003.wattso071
|View full text |Cite
|
Sign up to set email alerts
|

Sex Offender Treatment Skills and Approaches

Abstract: Offender work is generally carried out in a group setting, but programmes do not always take full advantage of the therapeutic potential of group treatment principles. This chapter briefly considers the highly developed literature on groupwork and presents a systematic application to sex offender treatment, not only as a vehicle by which to deliver programmes, but also as a complementary therapeutic instrument. This innovation involves the conscious and deliberate incorporation of knowledge and strategies asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…Ware, Frost, and Hoy (2010) reflected on this dilemma noting that one of the most important challenges for prison based treatment programs is how to address the causal or risk factors that contributed to the sex offending behaviour (skills that are to be used upon release) whilst also negating the harm caused, or difficulties created, by the prison environment (skills to be used whilst in prison). Frost, Ware, and Boer (2017) have also suggested that there are two necessary conditions in providing a positive prison climate during treatment to allow for content rehearsal and practiceparticularly in relation to interpersonal or relationship skills. First, there must be a "safe" and containing environment that is conducive to openness, directness and honesty and.…”
Section: During and After Treatmentmentioning
confidence: 99%
“…Ware, Frost, and Hoy (2010) reflected on this dilemma noting that one of the most important challenges for prison based treatment programs is how to address the causal or risk factors that contributed to the sex offending behaviour (skills that are to be used upon release) whilst also negating the harm caused, or difficulties created, by the prison environment (skills to be used whilst in prison). Frost, Ware, and Boer (2017) have also suggested that there are two necessary conditions in providing a positive prison climate during treatment to allow for content rehearsal and practiceparticularly in relation to interpersonal or relationship skills. First, there must be a "safe" and containing environment that is conducive to openness, directness and honesty and.…”
Section: During and After Treatmentmentioning
confidence: 99%